Pendekatan Moderasi Beragama dalam Mengatasi Konflik Sosial - Miftahul, Iqbal; Darmanto (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2024)
Social conflicts in Indonesia, particularly those triggered by religious differences, have become a significant challenge to the stability and harmony of society. Religious moderation, which emphasizes tolerance, inclusivity, and mutual respect, has emerged as a potential solution to mitigate these conflicts. The importance of religious moderation lies in its ability to foster interfaith dialogue, strengthen unity, and prevent radicalization that could lead to terrorism. This study aims to analyze the effectiveness of applying religious moderation in addressing social conflicts in Indonesia, focusing on case studies in several regions that frequently experience interfaith tensions. Through a qualitative approach, this research is expected to provide more effective policy recommendations for promoting harmony and social stability in Indonesia